Reconciling Educational Dualism in Indonesia: A Study of Islamic Education Integration into the National Education System (1945–Reform Era): (Rekonsiliasi Dualisme Pendidikan di Indonesia: Studi Integrasi Pendidikan Islam ke dalam Sistem Pendidikan Nasional (1945-Era Reformasi)) - Armydita Putri Permatasari; Devita Putri Alivia; Noerfidyah Zoelvani Khoiroenisyah (PT. Berkah Smart Academica, 2025)
Abstract: This study aims to comprehensively examine the dynamics and milestones in the development of Islamic education in Indonesia during the post-independence period. This study is a literature review (library research) originating from library materials using a qualitative-historical approach. Data exploration was conducted through the identification, in-depth analysis, and synthesis of historical documents, books, and scientific journals relevant to post-independence Islamic education policies and institutions. The results indicate that in the post-independence era, Islamic education received serious attention and formal recognition from the government, encompassing both public and private sectors. This was marked by the strategic repositioning of religion within the national education system and efforts toward the curricular integration of Islamic and general education. This integration led to the transformation of madrasahs and pesantren, which functioned not only as moral-religious strongholds but were also legally recognized as co-equal educational institutions capable of producing high-quality national human resources. Abstrak: Penelitian ini bertujuan untuk mengkaji secara komprehensif dinamika dan milstone perkembangan pendidikan Islam di Indonesia pada masa pasca-kemerdekaan. Penelitian ini merupakan studi pustaka (library research) yang bersumber dari bahan kepustakaan dengan menggunakan pendekatan kualitatif-historis. Eksplorasi data dilakukan melalui identifikasi, telaah mendalam, dan sintesis terhadap dokumen historis, buku, serta jurnal ilmiah yang relevan dengan kebijakan dan institusi pendidikan Islam pasca-kemerdekaan. Hasil penelitian menunjukkan bahwa setelah kemerdekaan, pendidikan Islam mendapatkan perhatian serius dan rekognisi formal dari pemerintah, baik untuk lembaga negeri maupun swasta. Hal ini ditandai dengan reposisi strategis agama dalam sistem pendidikan nasional, serta upaya integrasi kurikulum antara pendidikan Islam dan pendidikan umum. Integrasi ini bermuara pada transformasi madrasah dan pesantren, yang tidak hanya berfungsi sebagai benteng moral-keagamaan tetapi juga diakui secara yuridis-formal sebagai lembaga pendidikan yang setara dalam melahirkan sumber daya manusia nasional yang unggul.